Dio Cafe / Nurul Arwani Md. Zain ... [et al.] - Md. Zain, Nurul Arwani; Abdul Moin, Muna Munira; Saiman, Rayayu Putri Wijiana; Mohd Anta, Aqilah; Ismail, Nur Aina (2016)
Our business is based on partnership where it consists of five members which hold important positions in the company such as General Manager, Administrative Manager, Marketing Manager, Operational Manager and also Financial Manager. We have contributed a total of RM I 00,000 as our capital, where each member contributes RM 15,000 and the remaining RM 25,000 is from Bank Islam's loan. Dio Cafe unlike a typical cafe, we serve variety of delicious cookies, cakes and more for the Malaysian. The origin name of this company is from the Hungarian word, Dio- which means nuts. Our Cafe will be located at G-354, Ground Floor, I Borneo Hypermall, Jalan Sulaman 88450, Kota Kinabalu, Sabah. The reason we choose 1 Borneo is because it is the largest shopping complex in East Malaysia. 1 Borneo Hypermall is located in an area of the fastest growing sector in Sabah. Our target market of customers is general. It may come from all income level and from different levels of age. Even children can also enjoy to buy our products. Nuts are well known as nutritious snacks-particularly raw tree nuts, such as almonds, cashews, and walnuts which have been linked to lower cholesterol, better heart health, weight control and also a lower cancer risk. All the nuts have different nutrition and thus offer different health benefits. Unfortunately, as we go through with the changes of environment, people nowadays do not recognize the benefits of nuts. Nuts are considered as the second best option in the food world. They are often ignored in the light of being fattening despite the fact that they are super tasty and nutritious. Therefore, based on our observation and survey, we have decided to create Dio Cafe in order to encourage people to consume more nuts besides giving them additional general knowledge about the roles of nuts to our body. At the same time, Dio Cafe is full of surprises that will make it an interesting and attractive cafe compared to the existing cafe out there.